Program Peningkatan Resilience pada Orang Tua yang Memiliki Anak Pecandu Narkoba - Suhana Suhana (Universitas Islam Bandung, 2019)
S u h a n a. Curriculum design to improve parent Resilience with drugs abuser children (case study for parents with drugs abuser children in Inabah Suryalaya boarding school Tasikmalaya). Children is the greatest of gift for all parents, if the children sick, parent will arxious and doing things to make batter for the children, parents will also feel very proud if the children succeed. Now a days, drugs is threatening tenage and adults. Base on new fact from BNN, the last five years the use of drugs improving 3617 in 2001 become 17355 in 2005 or 34,4% per year or 20 case each day. The death of drugs abuser 15 about 41 people dies each day or almoust 2 people dies in each hour. It is not easy to have children who have drugs problem. The parents need to have resilience in dealing with adversity from the problem. The research question is